Respuesta :
The standard form:
[tex](x-3)^2+(y+5)^2=64[/tex].
Use: [tex](a\pm b)^2=a^2\pm2ab+b^2[/tex].
[tex]x^2-2\cdot x\cdot3+3^2+y^2+2\cdot y\cdot5+5^2=64\\\\x^2-6x+9+y^2+10y+25=64\ \ \ |-64\\\\x^2+y^2-6x+10y-39=0[/tex]
.
The general form.
[tex](x-3)^2+(y+5)^2=64[/tex].
Use: [tex](a\pm b)^2=a^2\pm2ab+b^2[/tex].
[tex]x^2-2\cdot x\cdot3+3^2+y^2+2\cdot y\cdot5+5^2=64\\\\x^2-6x+9+y^2+10y+25=64\ \ \ |-64\\\\x^2+y^2-6x+10y-39=0[/tex]
.
The general form.
Answer:
The equation [tex](x-3)^2+(y+5)^2=64[/tex] in standard form for the circle is [tex](x-3)^2+(y-(-5))^2=8^2[/tex]
Step-by-step explanation:
Given : Equation of circle as [tex](x-3)^2+(y+5)^2=64[/tex]
We have to write the equation in standard form for the circle.
The standard equation of circle with center (h,k) and radius r is given as
[tex](x-h)^2+(y-k)^2=r^2[/tex]
Consider the given equation [tex](x-3)^2+(y+5)^2=64[/tex]
64 can be written as 8²
Rewrite it in standard form as ,
[tex](x-3)^2+(y-(-5))^2=8^2[/tex]
where center is (3, - 5) and radius = 8
Thus, The equation [tex](x-3)^2+(y+5)^2=64[/tex] in standard form for the circle is [tex](x-3)^2+(y-(-5))^2=8^2[/tex]